Light-mediated regulation of phospholipid synthesis in Rhodopseudomonas sphaeroides. - Campbell, T B (1983)
The relationship between the culture levels of guanosine-5'-diphosphate-3'-diphosphate (ppGpp) and the rates of synthesis and accumulation of cellular phospholipids was examined in cultures of Rhodopseudomonas sphaeroides that had been subjected to immediate decreases in incident light intensity. After a high-to-low light transition of high-light-adapted cells, an immediate inhibition of total cellular phospholipid production occurred coincident with a rapid accumulation of culture ppGpp. The inhibition of phospholipid accumulation occurred at the level of phospholipid synthesis rather than turnover, and both the extent of ppGpp accumulation and the degree of inhibition of phospholipid synthesis were directly dependent upon the magnitude of the light transition. Maximum inhibition (greater than 90%) of the rate of cellular phospholipid synthesis occurred after transitions from 5,350 to 268 1x and lower, including transitions to the dark, with comparable inhibition being exerted upon the rates of synthesis of individual species of phospholipids. Reinitiation of culture phospholipid accumulation in cultures shifted from 5,350 to 1,070 1x and lower occurred 65 to 70 min subsequent to the downshift in light intensity, apparently irrespective of the culture level of ppGpp.